2020
DOI: 10.3174/ajnr.a6911
|View full text |Cite
|
Sign up to set email alerts
|

Non-EPI versus Multishot EPI DWI in Cholesteatoma Detection: Correlation with Operative Findings

Abstract: BACKGROUND AND PURPOSE: Although multishot EPI (readout-segmented EPI) has been touted as a robust DWI sequence for cholesteatoma evaluation, its efficacy in disease detection compared with a non-EPI (eg, HASTE) technique is unknown. This study sought to compare the accuracy of readout-segmented EPI with that of HASTE DWI in cholesteatoma detection. MATERIALS AND METHODS:A retrospective review was completed of consecutive patients who underwent MR imaging for the evaluation of suspected primary or recurrent/re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In our opinion, uncorrected rsDWI should not be considered equal to tseDWI in terms of diagnostic accuracy and confidence. This statement is confirmed by our results in this study, which are in accordance with a study by Benson et al [ 20 ]. In contrast, topupDWI showed an enhanced diagnostic performance and almost caught up with tseDWI.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our opinion, uncorrected rsDWI should not be considered equal to tseDWI in terms of diagnostic accuracy and confidence. This statement is confirmed by our results in this study, which are in accordance with a study by Benson et al [ 20 ]. In contrast, topupDWI showed an enhanced diagnostic performance and almost caught up with tseDWI.…”
Section: Discussionsupporting
confidence: 94%
“…Unfortunately, comparisons between rsDWI and tseDWI in cholesteatoma diagnostics led to contradictory results in recent studies. Dudau et al found a comparable diagnostic performance between both sequences [ 19 ], whereas Benson et al and Wiesmueller et al found superior diagnostic accuracy and image quality for tseDWI [ 20 , 21 ]. Although in the last-mentioned study, rsDWI showed superior subjective image quality; its diagnostic performance was significantly degraded by higher susceptibility-induced distortions leading to both lower sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…The presented data elaborated a higher degree of diagnostic reliability in HASTE DWI than in RESOLVE DWI (ie, non‐EPI vs. EPI DWI) sequences. This result corresponds to the findings observed in the study of Benson et al., in which they compared HASTE with readout‐segmented EPI sequences in 23 patients 21 . HASTE DWI has a long acquisition time of approximately 5 minutes.…”
Section: Discussionsupporting
confidence: 89%
“…These patients are currently surveilled postoperatively with a non-EPI DWI, which offers the most reliable imaging option for the surveillance of recidivistic or recurrent disease. 20 Given that the temporal bone is completely obstructed on non-EPI DWI in all but the Osia without magnet condition, evaluation of future imaging requirements for patients should be taken into consideration prior to implantation. Importantly, each episode of magnet removal requires 2 procedures, typically performed in the operating room under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%